AI-INTEGRATED DESMOS ACTIVITIES FOR UNDERSTANDING THE CONCEPT OF LINEAR EQUATIONS: AN INTRINSIC CASE STUDY - Claudya, Cindy; Fitriani, Fitriani; Faisal, Faisal; Anggreni, Fenny (Jurnal Pendidikan Matematika dan IPA, 2026)
Students’ conceptual understanding of mathematics, particularly linear equations, remains a challenge at SMP Negeri 1 Langsa. Preliminary observations show that students struggle to connect algebraic and graphical representations, leading learning to emphasize procedural calculations rather than conceptual understanding. Moreover, the digital learning media used are not yet adaptive or personalized, resulting in general feedback that does not address individual learning differences and misconceptions. This study aims to analyze how the integration of AI features in Desmos Activity can improve students’ conceptual understanding of straight-line equations. In this study, conceptual understanding is operationally defined as students’ ability to interpret, represent, and explain the relationships among slope (m), intercept (c), and the graphical form of linear equations, measured using a reflection rubric and misconception identification indicators. A qualitative intrinsic case study was conducted with 30 eighth-grade students and two mathematics teachers at SMP Negeri 1 Langsa. The intervention was carried out over four weeks consisting of eight class meetings, during which Desmos was integrated with an E-learning module equipped with an adaptive chatbot and a personalized exploration-path recommendation system. Data from observations, activity logs, and interviews show improved conceptual understanding, indicated by higher reflection scores (50%–80%) and increased module interaction, highlighting the effectiveness of AI-integrated Desmos Activity in supporting adaptive and personalized learning., thereby supporting the creation of adaptive mathematics learning environments at the junior high school level.